(untitled) (Swiss Medical Weekly, 2014)
OBJECTIVE: To provide an overview of heart allocation and transplantation in Switzerland since the introduction of the Swiss Organ Allocation System (SOAS). METHODS: This study is a retrospective analysis of SOAS data related to heart transplantation between 1 July 2007 and 30 June 30 2013. RESULTS: During the study period, 300 patients were newly waitlisted for a heart transplant in Switzerland, 199 were transplanted and 52 deceased while on the waiting list. Of the 723 hearts offered by Swisstransplant to the three university hospitals with a heart transplantation programme (Bern, Lausanne and Zurich), 199 (27.5%) were transplanted. Of these, 183 (92.0%) were procured in Switzerland and 16 (8.0%) were offered by a foreign organ procurement organisation. Fifty-two hearts were transplanted to patients who were listed in urgent status, equalling an urgent transplant rate of 26.1%. Whereas the overall waiting list mortality was 19.0%, it was as high as 31.8% in patients older than 60 years. CONCLUSIONS: Our study showed a growing Swiss heart transplant waiting list, as significantly more patients were newly waitlisted than transplanted. Compared with the international data, the acceptance rate of heart offers and the rate of urgent transplantations were relatively low, while the waiting list mortality was higher. The fact that the mortality was highest in candidates aged 60 and above suggests that the new generation of ventricular assist devices as destination therapy should be considered as an alternative to transplantation in selected patients.